Spatiotemporal and kinematic adjustments in master runners may be associated with the relative physiological effort during running - Jamkrajang, Parunchaya; Suwanmana, Sarit; Limroongreungrat, Weerawat; Verheul, Jasper (Frontiers in Sports and Active Living, 2023)
Master runners maintain a similar running economy to young runners, despite displaying biomechanical characteristics that are associated with a worse running economy. This apparent paradox may be explained by a greater physiological efforti.e., percentage of maximal oxygen uptake (VO2-max)that master runners perform at a given speed. Moreover, agerelated responses to non-exhaustive sustained running are yet underexplored. The aims of this study were, therefore, to examine if biomechanical adjustments in master runners are physiological-effort dependent, and to explore the age-related biomechanical changes during a non-exhaustive sustained run. Young (23.9 ± 6; n=12) and master (47.3 ± 6.9; n=12) runners performed a sustained 30-minute treadmill run matched for relative physiological effort (70% VO2-max), while spatiotemporal and lower-limb kinematic characteristics were collected during the 1 st and 30 th minute. Group differences were observed in step/stride length, knee touch-down angle, and knee stiffness. However, both groups of runners had a similar step frequency, vertical centre of mass oscillation, and knee range of motion. Age-related adjustment in these latter characteristics may thus not be an inevitable result of the aging process but rather a strategy to maintain running economy. The relative physiological effort of runners should, therefore, be considered when examining age-related adjustments in running biomechanics.